2003
DOI: 10.1002/jgm.407
|View full text |Cite
|
Sign up to set email alerts
|

A bicistronic SIN‐lentiviral vector containing G156A MGMT allows selection and metabolic correction of hematopoietic protoporphyric cell lines

Abstract: This study demonstrates that a lentiviral vector including therapeutic and G156A MGMT genes followed by BG/BCNU exposure can lead to a full metabolic correction of deficient cells. This vector might form the basis of new EPP mouse gene therapy protocols without a preconditioning regimen followed by in vivo selection of corrected hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…To avoid this problem, we recommend using the same promoter to drive both the selection marker and the transgene. An alternative approach is to use the bicistronic lentivector, which allows the expression of the target gene and the selection marker under the control of one common promoter (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this problem, we recommend using the same promoter to drive both the selection marker and the transgene. An alternative approach is to use the bicistronic lentivector, which allows the expression of the target gene and the selection marker under the control of one common promoter (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…This approach could have additional therapeutic applications in genetic diseases, as demonstrated in mouse models of thalassemia [ 65 ]; protoporphyria [ 66 ]; HIV therapy [ 67,68 ]; and graft modulation following allogeneic transplant. Importantly, it has recently been demonstrated that the effective chemoresistance and in vivo selection seen in murine models can be robustly recapitulated in large animal canine allograft and autograft models [ 39,62 ].…”
Section: Engineering Chemoresistancementioning
confidence: 99%
“…For erythropoietic protoporphiria ex vivo applications, Richard et al [148] have co-expressed the transgene of interest, i.e. the human FECH cDNA, with a human alkylating drug resistance mutant O(6)-methylguanine DNA methyltransferase.…”
Section: Multiple Gene Expression Designmentioning
confidence: 99%